Pengaruh Disiplin Kerja, Komitmen Organisasi, dan Lingkungan Kerja Terhadap Kinerja Pegawai MIN 1 Jombang - Akhmad Taqiyuddin; Lailatus Sa’adah; Diah Illun Nasikhah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
The purpose of this study was to determine the effect of work discipline, organizational commitment, and work environment on the performance of employees at MIN 1 Jombang. The method used in this research is a quantitative method. The population in this study amounted to 81 employees while the sample numbered 64 respondents using a purposive sampling technique. Data was collected using the questionnaire method, which was then analyzed using multiple regression analysis using SPSS version 26. The results showed that work discipline and organizational commitment partially did not affect employee performance, while work environment variables showed an effect on employee performance. Simultaneously the variables of work discipline, organizational commitment, and work environment have a positive effect on employee performance at MIN 1 Jombang. The results of the analysis of the coefficient of determination obtained 0.719 or 71.9%, which means that the contribution of work discipline, organizational commitment and work environment variables to employee performance is 71.9%, while the rest is influenced by other factors outside this regression model.